Land-use change from food to energy: meta-analysis unravels effects of bioenergy on biodiversity and cultural ecosystem services. (11th November 2021) - Donnison, Caspar; Holland, Robert A; Harris, Zoe M; Eigenbrod, Felix; Taylor, Gail
Abstract: Bioenergy has been identified as a key contributor to future energy scenarios consistent with the Paris Agreement targets, and is relied upon in scenarios both with and without bioenergy with carbon capture and storage, owing to the multiple ways in which bioenergy can substitute fossil fuels. Understanding the environmental and societal impacts of land-use change (LUC) to bioenergy crops is important in determining where and how they could be deployed, and the resulting trade-offs and co-benefits. We use systematic review and meta-analysis to assess the existing literature on two poorly understood impacts of this LUC that are likely to have an important effect on public acceptability: cultural ecosystem services and biodiversity. We focus on the impact of LUC to non-food bioenergy crops on agricultural landscapes, where large-scale bioenergy planting may be required. Our meta-analysis finds strong benefits for biodiversity overall (up 75% ± 13%), with particular benefits for bird abundance (+81% ± 32%), bird species richness (+100% ± 31%), arthropod abundance (+52% ± 36%), microbial biomass (+77% ± 24%), and plant species richness (+25% ± 22%), when land moves out of either arable crops or grassland to bioenergy production. Conversions from arable land to energy trees led to particularly strong benefits, providing an insight into how future LUC to non-food bioenergy crops could support biodiversity. There were inadequate data to complete a meta-analysis on the effects of non-food bioenergy crops on cultural ecosystem services, and few generalizable conclusions from a systematic review of the literature, however, findings highlight the importance of landscape context and planting strategies in determining impact. Our findings demonstrate improved farm-scale biodiversity on agricultural land with non-food bioenergy crops, but also limited knowledge concerning public response to this LUC, which could prove crucial to the successful expansion of bioenergy to meet the Paris targets.